From target group to actors of collective action: The empowerment process throughout a Participatory Evaluation project - Ciraso-Calí, Anna; Pineda-Herrero, Pilar; Úcar-Martínez, Xavier (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales)

(untitled) (Département de communication sociale et publique, Université du Québec à Montréal, 2015)
The main goal of this paper is to describe and analyze the individual and collective empowerment process of a group involved in a participatory evaluation project developed during 2012 in Badia del Vallès (Barcelona, Spain). The steering group was composed of university evaluators, neighbours of the municipality and local technicians or community workers, who attended 13 face-to-face sessions, focused on the evaluation of two different areas of community action: the area called «anti-crisis» and the area of non formal education. Results show that some attitudes changed radically during the process: for instance, the idea of participation shifted from a dependent vision towards a more active idea. Within the group, an important element was the acknowledgment of the other as a source of learning, which made possible the creation of a strong team. Moreover, the process facilitated the improvement of the members’ self-image, and consequently their self-esteem.